Vox populi, vox dei : escolhas sociais, regras de votação e impossibilidades - Bruno Rodrigues Pinheiro (2018)
The social choice theory is the study of the processes and procedures of collective decisions aimed understanding how a community (voters, legislators, court, committee, etc.) can achieve social preference based on the preferences of individual members. In a democracy, the classic way of making such decision is to enable each individual to express himself through the vote. However, since there are different voting rules, how we might find out what the preferences of all citizens are? The aim of this dissertation to make an argument between the normative political philosophy and social choice theory focusing on the impossibility theorem of Arrow (1951), Gibbard (1973), Satterthwaite (1975) and Sen (1970). To develop the argument, we present the theory of social choice in a historical perspective and the normative criteria of both the different voting rules and the main theorems. Although they are normative results with negative connotations, presents here as a collateral result, possibility dialogue between the social choice theory and the deliberationist approach of democracy.